The construction and validation of the primary scientific reasoning test - Diana, N (2018)
A major task of science education is to foster scientific reasoning. Despite extensive research, it is still unclear how best to assess this cognitive proficiency; a limited consensus of its nature has arguably constrained the development of classroom assessments of scientific reasoning. Therefore, this research aimed to develop a valid and reliable test of scientific reasoning – the Primary Scientific Reasoning Test (PSRT) – for primary-aged pupils. Developments in science education, as well as emerging and novel insights across substantive literature, formed the theoretical framework underlying the PSRT. A mixed methodology was used to develop and validate the PSRT over four phases. The first phase developed the theoretical framework and the draft items. In the next phase, an 18-member expert panel from Singapore and England evaluated and endorsed the conceptual validity of the construct and the content validity of the draft items. The third phase field-tested and refined the draft instrument with 138 Year 7 pupils from four Singapore secondary schools. In the fourth and last phase, 431 Year 6 pupils from six Singapore primary schools attempted the finalised 100-item PSRT. Results from psychometric analysis using Rasch modelling supported inferences of a unidimensional construct underlying the test, and examination of the item difficulty estimates produced evidence that the order of difficulties generally accorded with the framework of scientific reasoning. Given that the explanatory concepts in the framework generally explained the pupils’ performance and drawing on the strength and scope of other evidence, the thesis concludes that the PSRT displayed reasonably strong construct validity. This conclusion supports the use of PSRT as a valid and reliable measure of scientific reasoning for primary-aged pupils. The theoretical basis of the PSRT and its construction procedures also bear lessons for test developers and researchers. Overall, the study contributes clarification and understanding about the nature and assessment of scientific reasoning, particularly for primary-aged pupils.